Migration in times of pandemic: SARS-CoV-2 infection among the Warao indigenous refugees in Belém, Pará, Amazonia, Brazil - Hilton Pereira da Silva; Isabella Nogueira Abreu; Carlos Neandro Cordeiro Lima; Aline Cecy Rocha de Lima; Alexandre do Nascimento Barbosa; Lehi Rodrigues de Oliveira; Mayumi Aragão Fujishima; Sandra Souza Lima; Vitor Nina de Lima; Socorro Castelo-Branco; Antonio Carlos Rosário Vallinoto (BMC, 2021)
Abstract Background The emergence of the new causative agent of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in the city of Wuhan, China, in December 2019, and its spread worldwide, led the World Health Organization (WHO) to declare a pandemic. The disease has caused high mortality among traditional populations and the most socially vulnerable groups such indigenous and refugees. The present study aims to investigate the prevalence of anti-SARS-CoV-2 IgG antibodies in the population of Venezuelan indigenous Warao refugees residing in private and public shelters in the city of Belem, capital of Para State, in the Brazilian Amazon. Methods One hundred one individuals of both sexes (43 men and 58 women) with ages varying from 18 to 77 years (average of 36 years) were investigated. Whole blood samples were collected and subsequently separated into plasma and leukocytes. Serological analysis was performed using an enzyme-linked immunosorbent assay - ELISA (Anti-SARS-COV-2 S1 IgG, EUROIMMUN, USA). Results The results indicate a positive serum prevalence of 83.2% (84), of which 77.6% (45/58) were females and 90.7% (39/43) were males. An indeterminate profile was observed in 6.9% (7), where it was not possible to confirm the presence of antibodies, and 9.9% (10) individuals were negative for IgG antibodies. Conclusions The finding of the high seroprevalence of IgG anti-SARS-CoV-2 antibodies reveals a high exposure of the Warao population in Belem to infection with the new coronavirus. These results underscore the importance of maintaining epidemiological surveillance with testing in traditional populations due to the high possibility of spreading the virus, especially among the most socioeconomically vulnerable groups, which depend exclusively on the Unified Health System (SUS), such as refugees and indigenous people.